2019
DOI: 10.1016/j.jml.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Forget me not: Encoding processes in value-directed remembering

Abstract: Valuable items are often remembered better than less valuable items, but research on the mechanisms supporting this value effect is limited. In the current study, we sought to determine how items might be differentially encoded based on their value. In Experiment 1, participants studied words associated with point-values which were followed by a cue to either "Remember" the word for a later test or "Forget" the word. While to-beforgotten words were recognized at a lower rate than to-be-remembered words, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 39 publications
7
42
0
Order By: Relevance
“…These instructions may have encouraged participants to strategically encode the images, similar to work investigating explicit memory strategies for remembering rewarding events (e.g. Hennessee et al, 2019 ). Such explicit strategies may use different neural mechanisms than those motivating our questions, namely, the dopaminergic and noradrenergic modulation of hippocampal memories characterized in animal conditioning paradigms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These instructions may have encouraged participants to strategically encode the images, similar to work investigating explicit memory strategies for remembering rewarding events (e.g. Hennessee et al, 2019 ). Such explicit strategies may use different neural mechanisms than those motivating our questions, namely, the dopaminergic and noradrenergic modulation of hippocampal memories characterized in animal conditioning paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…In both Experiment 1 and the explicit memory version of Experiment 2, we incentivized participants to associate trial-unique images with their reward outcome: in the initial instructions, participants were told that they would later have an opportunity to choose between the images and win their reward outcomes again. These instructions may have encouraged participants to strategically encode the images, similar to work investigating explicit memory strategies for remembering rewarding events (e.g., Hennessee, Patterson, Castel, & Knowlton, 2019). Such explicit strategies may use different neural mechanisms than those motivating our questions, namely, the dopaminergic and noradrenergic modulation of hippocampal memories characterized in animal conditioning paradigms.…”
Section: Explicit Versus Implicit Memory Effectsmentioning
confidence: 99%
“…Indeed, Malmberg and Shiffrin reported that such operations did not result in list-composition effects. Yet rewarded items, which are known to capture processing resources during encoding (Hennessee et al, 2019), emotional items, which also capture encoding resources (Hadley & MacKay, 2006; Talmi et al, 2007; Talmi & McGarry, 2012), and experimental manipulations that increase item elaboration during encoding (McDaniel & Bugg, 2008), all give rise to list-composition effects even without overt repetition during study. Taken together, it may be the case that either spaced repetition or intra-item elaboration could give rise to two “flavour” of the list-composition effect, which SAM and eCMR account for, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there is strong evidence that reward can attract attention obligatorily, even against current goals (Bucker & Theeuwes, 2017). On the other hand, the recall advantage of high-reward information can be overcome when participants are instructed to allocate strategic, effortful resources to encoding all items, suggesting that reward recruits such strategies obligatorily (Hennessee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…But not all experiences are equally useful to remember — the information we encounter varies in its utility in helping us gain future reward. By adulthood, individuals demonstrate the ability to prioritize memory for information that is likely to be most rewarding in the future (Adcock et al, 2006; M. S. Cohen et al, 2014, 2019; Hennessee et al, 2019; Shigemune et al, 2014; Shohamy & Adcock, 2010; Wittmann et al, 2005). Children, however, demonstrate weaker memory selectivity, often remembering relatively inconsequential information at the expense of higher-value items or associations (Castel et al, 2011; Hanten et al, 2007; Nussenbaum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%